SPINOPELVIC VARIABILITY ACCORDING TO THE ROUSSOULY CLASSIFICATON CURVE TYPE - PRATALI,RAPHAEL DE REZENDE (2020)
ABSTRACT Objective To evaluate the variability of spinopelvic sagittal parameters and the distribution of lordosis in the lumbar spine in a sample of patients. Methods This is a cross-sectional study considering full-spine radiographs of a patient sample. The patients were classified according to the Roussouly classification and both radiographic spinopelvic alignment parameters and the lordosis measurement of each lumbar spinal segment were considered. The radiographic parameters were correlated with the Roussouly classification type. Results Ninety patients were included in the study. There was significant correlation between pelvic incidence (PI) and lumbar lordosis (LL) (R=0.89; p<0.0001). The values of PI were significantly higher in Roussouly types 3 and 4 than in types 1 and 2 (p<0.001), as were the values of LL L1-S1(p<0.001). Considering the total sample, 67% of LL L1-S1 was located between L4-S1, but with variations by the Roussouly classification curve types. Conclusion This study demonstrated a high correlation between the values of PI and LL, as well as the importance of the distal lumbar segment (L4-S1) in the overall value of LL L1-S1, which was even higher in patients with a lower PI value (Roussouly types 1 and 2). Level of evidence II; Retrospective analysis of a prospective database (Cohort); Diagnostic study.